Seleção e financiamento de alternativas para o desenvolvimento e comercialização de um portfólio de novas tecnologias - Leonardo Rodrigues Tavares (2011)
The R&D portfolio selection is one of the key drivers of the medium and long term success of most companies. Several studies have already discussed the factors that influence the project selection and budget allocation, and also how the projects should be managed in order to achieve better results. However, considering the complexity of the problem and the lack of a prevalent approach to it, many managers still rely on heuristics to support their decision process. The present work aims to discuss the selection and funding of alternatives during the process of forming a R&D portfolio. It is taken into account the fact that the development and commercialization phases are distinct and, therefore, should be managed appropriately as far as budget implications and information availability are concerned. Two decisions rules are analyzed for choosing products that must be funded in the development stage to maximize the utility of the commercialization stage. The approach is illustrated with a numerical example related with the biotechnology industry.